Online Learning Applications in Shaping Entrepreneurial Character: A Systematic Review - Aniek Suryanti Kusuma; Sutajaya, I Made; Sudiarta, I Gusti Putu (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
Currently, the challenges facing education include the quantity and quality development to globally competition, as well as producing human resources. Therefore, it is important to educate the younger generation, specifically high school students to become imaginative and creative. This systematic review aimed to focus on internet searching of entrepreneurship context related to character-in-making. The data were collected from three major databases i.e., google Scholar, Sinta, and Scopus database. The results showed that online learning help to shape students' character or behavior to promote entrepreneurial spirit. The results of this research also showed that institutional stakeholders easily select, sort, and compare the quality of applications. Nevertheless, the application or software is beneficial to children in terms of teaching and educating. From a commercial perspective, this software is beneficial because it provides income through purchase or rent. This qualitative descriptive study implies and highlights within its limitation that the emergence of entrepreneurs tends to improve the learning quality and the community economy. And there tend to be needed for educational facilities or software which affects the number of entrepreneurs engaged in teaching.